Motion Graphic Media Informasi Wisata Kompleks Percandian Muara Jambi - M Sayuti; Yusril; Syafwandi (fakultas Desain Koomunikasi visual, 2022)
Muara Jambi Temple Complex (KPMJ) is a national cultural heritage area located in Muaro Jambi Regency, Maro Sebo District. This KPMJ has a Buddhist pattern. With an area of ​​17.5 KM2 which stretches 7 KM along the Batanghari River near the East Coast of Jambi. KPMJ has nine main temple buildings, and various types of collections that are closely related to historical, cultural and religious values. In order to support the existence of KPMJ as a regional and national tourism potential, promotional media as well as digital-based information media (motion graphics) are needed so that they are able to attract and increase public enthusiasm for traveling to KPMJ. At the same time being able to contribute knowledge and educate the public to care for and maintain and preserve cultural heritage. The theories used in the creation of this motion graphic are color theory, motion graphic theory, narration, communication, typography, and cultural heritage tourism theory. The method used by the designer in creating this motion graphic is 4D (define, design, develop, and disseminate). The target audience in this design is teenagers to early adulthood. The supporting media are posters, brochures, stickers, mugs, key chains, entrance tickets, id-cards, t-shirts, hats and umbrellas.